Parents' Perceptions of Preschool Activities: Exploring Outdoor Play. Issue 7 (2nd October 2016) - Jayasuriya, Avanthi; Williams, Marcia; Edwards, Todd; Tandon, Pooja
ABSTRACT: Research Findings : Outdoor play is important for children's health and development, yet many preschool-age children in child care settings do not receive the recommended 60 min/day of outdoor play. Child care providers have previously described parent-related barriers to increasing outdoor playtime, including parents not providing appropriate clothing for their children and parents' preference for academics over active play. This study explored parent perceptions and knowledge of outdoor playtime in child care environments. On average, parents reported wanting their child to spend significantly more time playing outside during a full day of child care than the recommended minimum. However, more than half of parents reported that they did not know how much time their child actually spent playing outside, and 43% reported that they did not know their child care center's outdoor play policies. Practice or Policy : Child care providers may overperceive parent-related barriers to outdoor play. Parents generally support outdoor play for their preschooler during center-based child care but are not well informed about outdoor playtime and policies. Encouraging communication between parents and early childhood educators about these topics could lead to more universal support and strategies for promoting outdoor and active play opportunities for children, which are important for children's health and development.